2020
DOI: 10.1101/2020.09.08.287458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mental Chronometry of Speaking in Dialogue: Semantic Interference Turns into Facilitation

Abstract: Numerous studies demonstrate that the production of words is delayed when speakers process in temporal proximity semantically related words. Yet the experimental settings underlying this effect are different from those under which we typically speak. This study demonstrates that semantic interference disappears, and can even turn into facilitation, when semantically related words are embedded in a meaningful communicative exchange. Experiment 1 and 3 (each N=32 university students) implemented a picture-word i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…[39] found a reduced semantic interference effect in a condition in which participants named pictures and were (falsely) told they had a partner in another room who read the superimposed distractor words (see also [40]). Similarly, Kuhlen & Abdel Rahman [41] found that when the PWI task is embedded in a communicative game, with one participant naming the distractor words and the other, co-present participant naming the pictures, semantic interference is greatly reduced (compared with a non-communicative, standard version of the PWI task). A possible reason is that naming pictures in a communicative setting enhances semantic facilitation at the conceptual level (due to distractor and target belonging to the same semantic category).…”
Section: Introductionmentioning
confidence: 93%
“…[39] found a reduced semantic interference effect in a condition in which participants named pictures and were (falsely) told they had a partner in another room who read the superimposed distractor words (see also [40]). Similarly, Kuhlen & Abdel Rahman [41] found that when the PWI task is embedded in a communicative game, with one participant naming the distractor words and the other, co-present participant naming the pictures, semantic interference is greatly reduced (compared with a non-communicative, standard version of the PWI task). A possible reason is that naming pictures in a communicative setting enhances semantic facilitation at the conceptual level (due to distractor and target belonging to the same semantic category).…”
Section: Introductionmentioning
confidence: 93%
“…[39] found a reduced semantic interference effect in a condition in which participants named pictures and were (falsely) told they had a partner in another room who read the superimposed distractor words (see also [40]). Similarly, Kuhlen & Abdel Rahman [41] found that when the PWI task is embedded in a communicative game, with one participant naming the distractor words and the other, co-present participant naming the pictures, semantic interference is greatly reduced (compared with a non-communicative, standard version of the PWI task). A possible reason is that naming pictures in a communicative setting enhances semantic facilitation at the conceptual level (due to distractor and target belonging to the same semantic category).…”
Section: Introductionmentioning
confidence: 99%
“…in Stroop, the task-irrelevant stimulus is spatially co-located with the task-relevant stimulus and strongly activates the interfering response), evidence for reduced perceptual conflict in the joint task of Demiral et al . [6] and evidence for reduced interference in joint PWI tasks [3941] means it is unclear whether one would expect joint Stroop interference to increase or decrease in a joint compared with an individual go-no-go version of the task.…”
Section: Introductionmentioning
confidence: 99%